2015
DOI: 10.1016/j.pmedr.2015.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Perceived health status associated with transport choice for short distance trips

Abstract: BackgroundThis study examines the association between active transport and perceived general health, perceived psychological wellbeing and a healthy body weight in the Netherlands.MethodsData were collected by an online questionnaire (N = 3663) in the Netherlands. Data collection was conducted over a period of one calendar year starting July 2012. Logistic regression analyses were used to investigate the association between choice of transport mode (bicycling vs car use and walking vs car use) and perceived ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Bicycle use showed the most robust results throughout all the different analyses. Our results are in line with previous studies that associated bicycle use with better health outcomes: perceived general health (Scheepers et al, 2015), perceived stress (Avila-Palencia et al, 2017), mental well-being (Martin et al, 2014;Mytton et al, 2016), and quality of life (de Geus et al, 2008). Qualitative research has suggested that choice of travel mode may affect well-being due to the fact that travelling (mainly commuting) can be perceived as a relaxing or transitional time between home and work life, which can also be about enjoying pleasant landscape, nature, and wildlife (Guell and Ogilvie, 2015).…”
Section: Comparison With Previous Studiessupporting
confidence: 93%
See 1 more Smart Citation
“…Bicycle use showed the most robust results throughout all the different analyses. Our results are in line with previous studies that associated bicycle use with better health outcomes: perceived general health (Scheepers et al, 2015), perceived stress (Avila-Palencia et al, 2017), mental well-being (Martin et al, 2014;Mytton et al, 2016), and quality of life (de Geus et al, 2008). Qualitative research has suggested that choice of travel mode may affect well-being due to the fact that travelling (mainly commuting) can be perceived as a relaxing or transitional time between home and work life, which can also be about enjoying pleasant landscape, nature, and wildlife (Guell and Ogilvie, 2015).…”
Section: Comparison With Previous Studiessupporting
confidence: 93%
“…On the other hand, Richards et al 2015 found small positive associations with happiness for walking, but no significant associations for the transport domain. Scheepers et al 2015 found that, in comparison with car use, walking was neither associated with perceived general health nor with psychological well-being. Also Mytton et al 2016 did not find statistically significant associations between walking and mental well-being.…”
Section: Comparison With Previous Studiesmentioning
confidence: 80%
“…Additionally, the influence of car access and socio-demographic characteristics are examined in this study. Furthermore, the correlation of body mass index (BMI) with active travel such as walking/biking and use of public transportation has been examined in several studies, with most finding a connection between lower BMI or a healthy body weight and active travel [40,41,42,43,44,45,46]. That being said, however, other studies reported limited evidence of association between adult BMI and active transport [47] and none between public transport accessibility and obesity [48].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to a low PA level, adults with chronic diseases with a high or moderate PA level had a better QOL (Abdelbasset et al, 2019;Pengpid & Peltzer, 2019). Previous cross-sectional studies also revealed that there was a significant positive association between transport-related PA levels and QOL (Humphreys et al, 2013;Scheepers et al, 2015). Individuals who choose walking, cycling, and public transportation as a major transport mode have higher life satisfaction, mental health, and QOL (Chng et al, 2016;Insall, 2013).…”
Section: Discussionmentioning
confidence: 94%